2022
DOI: 10.1038/s41467-022-34676-w
|View full text |Cite|
|
Sign up to set email alerts
|

Elective nodal irradiation mitigates local and systemic immunity generated by combination radiation and immunotherapy in head and neck tumors

Abstract: In the setting of conventional radiation therapy, even when combined with immunotherapy, head and neck cancer often recurs locally and regionally. Elective nodal irradiation (ENI) is commonly employed to decrease regional recurrence. Given our developing understanding that immune cells are radio-sensitive, and that T cell priming occurs in the draining lymph nodes (DLNs), we hypothesize that radiation therapy directed at the primary tumor only will increase the effectiveness of immunotherapies. We find that EN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 63 publications
5
44
0
2
Order By: Relevance
“…However, there is concern that the tumor draining lymph nodes should be spared from radiation therapy, as these are the sites of immune cell activation and expansion. [ 57,58 ] Consistent with this, our results suggest that nodal irradiation can be counter‐productive in patients with tumors that have low antigen production, because of toxic effects on proliferating T cells in the active nodes. This effect is less prominent when tumor antigen production is high because nT‐cell activation is more frequent, and not rate‐limiting.…”
Section: Discussionsupporting
confidence: 85%
“…However, there is concern that the tumor draining lymph nodes should be spared from radiation therapy, as these are the sites of immune cell activation and expansion. [ 57,58 ] Consistent with this, our results suggest that nodal irradiation can be counter‐productive in patients with tumors that have low antigen production, because of toxic effects on proliferating T cells in the active nodes. This effect is less prominent when tumor antigen production is high because nT‐cell activation is more frequent, and not rate‐limiting.…”
Section: Discussionsupporting
confidence: 85%
“…Recently two different head and neck studies highlight that lymphatic preserving treatments favor systemic antitumor immunity, whereas elective nodal irradiation may decrease immune cell functionality. 41 , 42 One may argue that this was the case of conventionally fractionated RT (Group-3) where both prostatic bed and pelvic lymph nodes were irradiated. Sini et al 43 has shown how whole pelvis RT in PCa can induce hematological toxicity, and the use of specific constraints on bone marrow may help limiting this effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, once immune memory is established, anti‐tumour immunity ceases to rely on TDLNs. Radiation therapy solely targeting the primary tumour can enhance the effectiveness of immunotherapy, while selective radiation targeting the lymph nodes can mitgate this effect 95 . Saddawi et al.…”
Section: Dilemmas and Prospectsmentioning
confidence: 99%
“…Radiation therapy solely targeting the primary tumour can enhance the effectiveness of immunotherapy, while selective radiation targeting the lymph nodes can mitgate this effect. 95 Saddawi et al conducted an additional preclinical study probing the role of TDLNs in immune checkpoint inhibitor (ICI) therapy. Employing a murine model in this experiment, they observed that the surgical removal of lymph nodes prior to ICI therapy significantly decreased overall survival rates.…”
Section: The Role Of Tdlns In Immunotherapy For Osccmentioning
confidence: 99%